Environmental factor and inflammation-driven alteration of the total peripheral T-cell compartment in granulomatosis with polyangiitis. (March 2017) - Kerstein, Anja; Schüler, Silke; Cabral-Marques, Otávio; Fazio, Juliane; Häsler, Robert; Müller, Antje; Pitann, Silke; Moosig, Frank; Klapa, Sebastian; Haas, Christian; Kabelitz, Dieter; Riemekasten, Gabriela; et al.
Abstract: Autoimmune diseases are initiated by a combination of predisposing genetic and environmental factors resulting in self-perpetuating chronic inflammation and tissue damage. Autoantibody production and an imbalance of effector and regulatory T-cells are hallmarks of autoimmune dysregulation. While expansion of circulating effector memory T-cells is linked to disease pathogenesis and progression, the causes driving alterations of the peripheral T-cell compartment have remained poorly understood so far. In granulomatosis with polyangiitis (GPA), a prototypical autoimmune disorder of unknown aetiology, we performed for the first time a combined approach using phenotyping, transcriptome and functional analyses of T-cell populations to evaluate triggers of memory T-cell expansion. In more detail, we found increased percentages of circulating CD4+CD28−, CD8+CD28− and CD4+CD161+ single-positive and CD4+CD8+ double-positive T-cells in GPA. Transcriptomic profiling of sorted T-cell populations showed major differences between GPA and healthy controls reflecting antigen- (bacteria, viruses, fungi) and cytokine-driven impact on T-cell populations in GPA. Concomitant cytomegalovirus (CMV) and Epstein-Barr virus (EBV) - positivity was associated with a significant increase in the percentage of CD28− T-cells in GPA-patients compared to sole CMV- or EBV-positivity or CMV- and EBV-negativity. T-cells specific for other viruses (influenza A virus, metapneumovirus, respiratory syncytial virus) and the autoantigen proteinase 3 (PR3) were infrequently detected in GPA. Antigen-specific T-cells were not specifically enriched in any of the T-cell subsets. Altogether, on a genetic and cellular basis, here we show that alterations of the peripheral T-cell compartment are driven by inflammation and various environmental factors including concomitant CMV and EBV infection. Our study provides novel insights into mechanisms driving autoimmune disease and on potential therapeutic targets. Highlights: Expansion of circulating CD28−, CD161+, and CD4+CD8+ T-cell populations in GPA. Concomitant CMV/EBV-positivity associated with expansion of CD28− T-cells in GPA. Environmental factors and inflammation impact on T-cell alterations in GPA.